A Questão da colisão de direitos e a ponderação: a construção de um método e a aplicação ao julgamento das ações diretas de inconstitucionalidade nº 6.586/DF e 6.587/DF - SOARES, Ana Luísa Brabo (2022)
This undergraduate thesis will discuss the Theory of Fundamental Rights and the conceptual aspects referring to rules and principles. At first, it will mention the historical evolution of natural law to contemporary constitutional law, and after, it will discuss the species of norms and the balance of the rights stemming from an analysis of the proportionality rule. Finally, to illustrate the theoretical bases presented, the context of the Covid-19 pandemic and the judgment of Direct Actions of Unconstitutionality n. 6.586/DF and 6.587/DF were used to show how to decide in a case of clash between the rights to collective health, freedom of choice and self-determination to not be vaccinated.